2008
DOI: 10.1002/anie.200801188
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced π Conjugation around a Porphyrin[6] Nanoring

Abstract: Dedicated to Professor Jeremy Sanders on the occasion of his 60th birthdayBelt-shaped chromophores provide fascinating insights into electronic p delocalization over curved surfaces with radially oriented p orbitals.[1] Examples include the cyclic para-phenylacetylenes [2] and the [4 6 ]paracyclophanedodecayne of Tsuji and coworkers, [3] as well as fullerenes and carbon nanotubes. A variety of belt-shaped porphyrin arrays have been synthesized; [4] however, the vast majority of them lacks a complete pconjugati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(151 citation statements)
references
References 24 publications
6
137
2
6
Order By: Relevance
“…We investigated the palladium-catalysed oxidative coupling of the linear zinc-porphyrin 10-mer l-P10 in the presence of hexa-pyridyl template T6 23,34 and octa-pyridyl template T8 35 ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the palladium-catalysed oxidative coupling of the linear zinc-porphyrin 10-mer l-P10 in the presence of hexa-pyridyl template T6 23,34 and octa-pyridyl template T8 35 ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Using this approach, Anderson and co-workers have described an efficient templated synthesis of the strained π conjugated D 6h porphyrin [6] nanoring 518 where the template 517 is bonded to the building blocks 516 by the formation of Zn−N(pyridine) bonds. 506 The stepwise effective molarities justify the good macrocyclization yields (33−44%) ( Figure 160). 507 It was found that the effective molarity in the presence of the hexameric template 517 is in the range 100−1000 M and they have demonstrated that this is a cooperative process; i.e., each step is more favored than the previous one.…”
Section: Other Templates In Macrocyclizationsmentioning
confidence: 96%
“…Templated porphyrin [6] nanoring synthesis. 506,507 Chemical Reviews Review DOI: 10.1021/acs.chemrev.5b00056…”
Section: Other Templates In Macrocyclizationsmentioning
confidence: 99%
“…[66,67] Worth mentioning are also the great variety of stable metallamacrocycles, obtained largely by insertion of Pt(II) into the dehydroannulenes under formation of bis(s-alkynyl)Pt(II) linkers. [68,69] While all these efforts have not led to regular 2D all-carbon polymers, which currently remain ''just a dream of synthetic chemists,'' [70] the search for new modifications of carbon has produced several new classes of macrocycles that feature conjugated all-carbon backbones without annellated benzene rings and display highly interesting optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%